The structure of Lithuanian infixed and sta-stem verbs (type CaC-) - Pakalniškienė, Dalia (Baltistica, 2024)
This article analyses the formal structure of infixed and sta-stem verbs (here and below – INSTA verbs) of the CaC- type in order to identify the typical traits of these lexemes in terms of their expression as well as their interconnection. A complex analysis of the formal expression of INSTA verbs revealed several interactions: a close connection between the root vocalism and consonant structure, the influence of the phonemic structure on the morphological structure of the verbs in question, and the impact on the formation of structural verb patterns. The results of the study justify the principle of grouping INSTA verbs according to root vocalism: such an approach makes it possible to identify the unique features of the formal structure, semantics, word-formation, and origin of INSTA verbs with different vocalism.